Composite diaphragm as well as preparation method and application thereof
By coating the modified coating of β"-Al2O3 and binder on the glass fiber membrane, the density and anti-dendrite penetration ability of the composite separator are improved, and the insufficient dendrite penetration in sodium ion batteries is solved. The problem has significantly improved the cycle stability and capacity retention rate of the battery.
Patent Information
- Application Number
- CN202411321033.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
The mechanical properties of glass fiber membranes in sodium ion batteries are poor, resulting in insufficient penetration of dendrites, affecting the cycling stability of the battery.
The composite diaphragm with a laminated glass fiber film and a modified coating is adopted. The modified coating includes β"-Al2O3 and an adhesive. The adhesive adheres to the surface of the glass fiber film to improve the density and resistance of the composite diaphragm. Dentite penetration ability.
It significantly improves the cycle stability and capacity retention rate of the battery, avoids the occurrence of micro-short circuits of the battery, and enhances the mechanical properties of the battery.
Smart Images

Figure CN119208913A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary battery diaphragms, and in particular relates to a composite diaphragm and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have not yet fully entered people's lives, while lithium-ion batteries, which came out almost at the same time as sodium-ion batteries, have been widely used in power batteries, energy storage, and electronic devices. The reason may be that the key technical parameters of sodium-ion batteries have not yet achieved a breakthrough recognized by the market. Battery separators are key components of batteries. The separators that can be used in sodium-ion batteries are mainly glass fiber membranes. According to experimental research, glass fiber membranes have excellent thermal stability, large porosity, good wettability, and relatively stable chemical properties, and are widely used in sodium-ion batteries. Due to the shortcomings of glass fiber membranes, such as soft texture, large pores, and poor mechanical properties, sodium dendrites are more likely to penetrate the separator during battery packaging and circulation, resulting in unstable coulombic efficiency of the battery. Therefore, how to improve the resistance of glass fiber membranes to dendrite penetration, thereby improving the cycle stability of sodium-ion batteries, has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0003] The purpose of the present invention is to provide a composite diaphragm and a preparation method and application thereof. The composite diaphragm provided by the present invention has excellent resistance to dendrite penetration, and the prepared sodium ion battery has excellent cycle stability.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a composite diaphragm, comprising a laminated glass fiber membrane and a modified coating;
[0006] The components of the modified coating include β"-Al2O3 and a binder.
[0007] Preferably, the mass ratio of the β"-Al2O3 to the binder is (2-9):1.
[0008] Preferably, the thickness of the modified coating is 20-40 μm; the thickness of the glass fiber membrane is 0.4-2 mm.
[0009] The present invention also provides a method for preparing the composite diaphragm described in the above technical solution, comprising the following steps:
[0010] (1) mixing β"-Al2O3, a binder and a solvent to obtain a mixed suspension;
[0011] (2) coating the mixed suspension obtained in step (1) on the surface of the glass fiber membrane to obtain a composite diaphragm.
[0012] Preferably, the particle size of β"-Al2O3 in step (1) is 0.1-1 μm.
[0013] Preferably, in step (1), the mass ratio of the binder to the solvent is (2-3): (97-98).
[0014] Preferably, the mixing in step (1) is ball milling mixing.
[0015] Preferably, the rotation speed of the ball milling is 200 to 500 rpm, and the time of the ball milling is 2 to 8 hours.
[0016] Preferably, the coating in step (2) is by blade coating.
[0017] The present invention also provides the use of the composite diaphragm described in the above technical solution or the composite diaphragm prepared by the preparation method described in the above technical solution in a secondary battery diaphragm.
[0018] The present invention provides a composite diaphragm, comprising a stacked glass fiber membrane and a modified coating; the components of the modified coating include β"-Al2O3 and a binder. The present invention uses β"-Al2O3 with good chemical inertness and thermal stability to modify the surface of the glass fiber membrane, and the binder is adhered to the surface of the glass fiber membrane. The density of the modified composite diaphragm is improved, thereby improving the strength of the composite diaphragm, and then improving the ability to resist dendrite penetration, which can significantly improve the cycle stability of the battery, avoid the occurrence of battery micro-short circuits, and improve the capacity retention rate of the battery. Experimental results show that sodium vanadium fluorophosphate is used as the positive electrode, metallic sodium is used as the negative electrode, the composite diaphragm of the present invention is used as the diaphragm, the modified coating is in contact with the negative electrode, the electrolyte is 1MNaClO4 in PC, and a battery is assembled. The battery still has a capacity retention rate of 70 to 79.04% after 1000 cycles at a rate of 5C. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a scanning electron microscope image of the glass fiber membrane in Example 1;
[0020] Figure 2 This is a scanning electron microscope image of the modified coating in the composite diaphragm prepared in Example 1;
[0021] Figure 3 This is a macroscopic image of the glass fiber membrane in Example 1 and the modified coating in the prepared composite diaphragm;
[0022] Figure 4 The coulombic efficiency of a battery assembled with the glass fiber membrane in Example 1 and the prepared composite membrane as the separator after 500 cycles at a rate of 5C;
[0023] Figure 5It is the discharge specific capacity of a battery assembled with the glass fiber membrane in Example 1 and the prepared composite membrane as separators and cycled 500 times at a rate of 5C. DETAILED DESCRIPTION
[0024] The present invention provides a composite diaphragm, comprising a laminated glass fiber membrane and a modified coating;
[0025] The components of the modified coating include β"-Al2O3 and a binder.
[0026] In the present invention, the composite membrane comprises a glass fiber membrane. In the present invention, the glass fiber membrane has excellent thermal stability, large porosity, good wettability and relatively stable chemical properties.
[0027] In the present invention, the thickness of the glass fiber membrane is preferably 0.4 to 2 mm, more preferably 0.6 to 0.8 mm.
[0028] In the present invention, the composite diaphragm also includes a modified coating adjacent to the glass fiber membrane; the components of the modified coating include β"-Al2O3 and a binder. The present invention uses β"-Al2O3 with good chemical inertness and thermal stability to modify the surface of the glass fiber membrane, and adheres to the surface of the glass fiber membrane through the binder. The density of the modified composite diaphragm is improved, thereby improving the strength of the composite diaphragm, and then improving the ability to resist dendrite penetration, which can significantly improve the cycle stability of the battery, avoid the occurrence of battery micro-short circuits, and improve the capacity retention rate of the battery.
[0029] In the present invention, the binder is preferably PVDF; the mass ratio of the β"-Al2O3 and the binder is preferably (2-9):1, further preferably (6-9):1, and more preferably (7-9):1. The present invention limits the mass ratio of β"-Al2O3 and the binder to the above range, which can further improve the density of the composite diaphragm, thereby further improving the mechanical properties.
[0030] In the present invention, the thickness of the modified coating is preferably 10 to 30 μm, more preferably 20 to 26 μm.
[0031] In the present invention, the thickness of the composite diaphragm is preferably 0.6 to 1 mm.
[0032] The present invention uses β"-Al2O3 with good chemical inertness and thermal stability to modify the surface of the glass fiber membrane, and adheres to the surface of the glass fiber membrane through a binder. The density of the modified composite diaphragm is improved, thereby improving the strength of the composite diaphragm, and further improving the anti-dendrite penetration ability, which can significantly improve the cycle stability of the battery, avoid the occurrence of battery micro-short circuits, and improve the capacity retention rate of the battery.
[0033] The composite diaphragm provided by the present invention has a dense surface, high mechanical strength, strong resistance to dendrite penetration, and a significant effect on improving battery cycle stability. Especially when the electrode material is not strongly adhered to the current collector and is easy to fall off, it can effectively avoid battery micro-short circuits caused by the detached electrode material penetrating the diaphragm. The preparation process is green and pollution-free, the raw materials are widely available, and the price is low.
[0034] The present invention takes an ordinary glass fiber membrane as an improvement object, improves the performance of the glass fiber membrane in view of its shortcomings such as large pores and uneven pore distribution, and coats the surface of the glass fiber membrane with electrochemical inertness β"-Al2O3 inorganic powder to obtain a stabilized modified diaphragm, thereby achieving the purpose of stabilizing the cycle stability of the sodium ion battery; the modified glass fiber membrane becomes denser, the diaphragm strength is enhanced, and the positive electrode material particles that may fall off can be confined in the positive electrode side, so that the particles continue to provide capacity for the battery, avoiding the occurrence of battery micro-short circuits, and improving the capacity retention rate of the battery.
[0035] The present invention also provides a method for preparing the composite diaphragm described in the above technical solution, comprising the following steps:
[0036] (1) mixing β"-Al2O3, a binder and a solvent to obtain a mixed suspension;
[0037] (2) coating the mixed suspension obtained in step (1) on the surface of the glass fiber membrane to obtain a composite diaphragm.
[0038] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.
[0039] The invention mixes β"-Al2O3, a binder and a solvent to obtain a mixed suspension.
[0040] In the present invention, the particle size of the β"-Al2O3 is preferably 0.1 to 1 μm.
[0041] In the present invention, the preparation method of β"-Al2O3 preferably comprises the following steps:
[0042] 1) mixing a sodium source, a magnesium source, an aluminum source and an organic solvent to obtain a slurry;
[0043] 2) The slurry obtained in step 1) is dried and calcined in sequence to obtain β"-Al2O3.
[0044] In the present invention, the sodium source, the magnesium source, the aluminum source and the organic solvent are preferably mixed to obtain a slurry.
[0045] In the present invention, the sodium source is preferably Na2CO3 and / or CH3COONa; the magnesium source is preferably MgO and / or MgSO4; and the aluminum source is preferably α-Al2O3 and / or γ-Al2O3.
[0046] The present invention has no particular limitation on the ratio of the sodium source, magnesium source and aluminum source. 0.67 Na 1.67 Al 10.33 O 17 Just mix the raw materials according to the standard formula.
[0047] In the present invention, the organic solvent is preferably ethanol. The present invention has no particular limitation on the amount of the organic solvent used, as long as it forms a paste-like slurry.
[0048] In the present invention, the mixing of the sodium source, magnesium source, aluminum source and organic solvent is preferably ball milling; the rotation speed of the ball milling is preferably 200 to 500 rpm, more preferably 300 to 400 rpm; the time of the ball milling is preferably 1 to 8 hours, more preferably 5 to 6 hours. The ball milling of the present invention can make the raw materials mixed more uniformly.
[0049] After obtaining the slurry, the present invention preferably sequentially dries and calcines the slurry to obtain β"-Al2O3.
[0050] In the present invention, the drying temperature is preferably 60 to 100° C., more preferably 80 to 100° C.; the drying time is preferably 4 to 12 hours, more preferably 8 to 10 hours. The present invention uses drying to remove the organic solvent in the slurry.
[0051] In the present invention, the calcination temperature is preferably 1000-1500° C., more preferably 1150-1220° C., and more preferably 1200° C.; the calcination time is preferably 1-4 h, and more preferably 1.5-2 h.
[0052] After calcination, the present invention preferably performs ball milling and drying on the calcined product in sequence to obtain β"-Al2O3. The present invention adopts ball milling and drying to obtain β"-Al2O3 powder with uniform particle size.
[0053] In the present invention, the rotation speed of the ball mill is preferably 200-500 rpm, more preferably 300-400 rpm; the time of the ball mill is preferably 4-10 hours, more preferably 6-8 hours; the ball milling medium of the ball mill is preferably ethanol. The ball milling of the present invention can make the raw materials mixed more uniformly.
[0054] The present invention has no particular limitation on the amount of ethanol used, and any amount known to those skilled in the art may be used.
[0055] In the present invention, the drying temperature is preferably 60 to 100° C., more preferably 80 to 100° C.; the drying time is preferably 4 to 12 hours, more preferably 8 to 10 hours. The present invention adopts drying to remove the ball milling media.
[0056] In the present invention, the solvent is preferably an organic solvent, more preferably NMP; the mass ratio of the binder to the solvent is preferably (2-3):(97-98), more preferably 2.5:97.5.
[0057] In the present invention, the mixing of the β"-Al2O3, the binder and the solvent is preferably ball milling; the rotation speed of the ball milling is preferably 200-500 rpm, more preferably 300-400 rpm; the time of the ball milling is preferably 2-8 h, more preferably 6-8 h.
[0058] After obtaining the mixed suspension, the present invention coats the mixed suspension on the surface of the glass fiber membrane to obtain a composite diaphragm.
[0059] In the present invention, the coating is preferably scraping, and the thickness of the scraping is preferably 70 to 80 μm, more preferably 75 μm. The present invention has no special limitation on the scraping operation, and the operation well known to those skilled in the art can be adopted.
[0060] After coating is completed, the present invention preferably dries the coated product to obtain a composite diaphragm.
[0061] In the present invention, the drying temperature is preferably 60 to 100° C., more preferably 60 to 80° C.; the drying time is preferably 4 to 12 hours, more preferably 6 to 8 hours. The present invention uses drying to remove the solvent in the film.
[0062] The preparation method provided by the present invention has simple process steps, does not require complicated processes, has low equipment requirements, is easy to operate, has low cost, and is environmentally friendly. The prepared composite diaphragm has a denser surface, better mechanical strength and better resistance to dendrite penetration, and can effectively improve the cycle stability and capacity retention rate of the battery, especially in secondary batteries with poor cycle performance.
[0063] The raw materials involved in the present invention are inexpensive, easy to obtain, and green and pollution-free. Compared with ordinary glass fiber diaphragms, the prepared composite diaphragm material can significantly reduce the risk of dendrite penetration of metal electrodes, and can effectively avoid the occurrence of battery micro-short circuits and thus stabilize the coulombic efficiency of the battery during the cycle. For the disadvantage of the widely used glass fiber membranes with large pores, a layer of dense inorganic coating can effectively confine the electrode material that may fall off to one side, effectively reduce the capacity decay rate, and thus improve the capacity retention rate of the battery during the cycle.
[0064] The present invention also provides the use of the composite diaphragm described in the above technical solution or the composite diaphragm prepared by the preparation method described in the above technical solution in a secondary battery diaphragm.
[0065] The present invention has no special limitation on the operation of applying the composite separator in a secondary battery separator, and the operation well known to those skilled in the art can be adopted.
[0066] The composite diaphragm provided by the present invention can be used as a secondary battery diaphragm, can improve the battery cycle stability, increase the battery capacity retention rate, and stabilize the battery coulomb efficiency.
[0067] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0068] Example 1
[0069] The composite diaphragm is composed of a glass fiber membrane and a modified coating layer arranged in layers;
[0070] The modified coating comprises β"-Al2O3 and PVDF, and the mass ratio of β"-Al2O3 to PVDF is 7:1;
[0071] The thickness of the modified coating is 20 μm; the thickness of the glass fiber membrane is 0.8 mm;
[0072] The preparation method of the composite diaphragm comprises the following steps:
[0073] (1) Mg 0.67 Na 1.67 Al 10.33 O 17 For the standard formula, α-Al2O3, MgO and Na2CO3 were weighed, placed in an agate ball mill, ethanol was added, and ball milled at 400 rpm for 4 h to obtain a slurry;
[0074] (2) drying the slurry obtained in step (1) in a drying oven at 60° C. for 8 h, then placing it in a muffle furnace and calcining it at 1220° C. for 1.5 h, then placing it in a ball mill again, adding ethanol, ball milling at 400 rpm for 4 h, and then drying it in a drying oven at 60° C. for 8 h to obtain β"-Al2O3 powder with a particle size of 0.1 to 1 μm;
[0075] (3) placing the β"-Al2O3 powder obtained in step (2) and PVDF in a ball mill, dropping NMP, and ball milling at 400 rpm for 8 h to obtain a mixed suspension; wherein the mass ratio of PVDF to NMP is 2.5:97.5;
[0076] (4) The mixed suspension obtained in step (3) is evenly coated on one side of the ultrafine glass fiber diaphragm of the power source battery using a scraper, and then placed in a 70° C. oven for drying for 8 hours to obtain a composite diaphragm; wherein the ultrafine glass fiber diaphragm of the power source battery is produced by Qicaiguan; and the coating thickness is 75 μm.
[0077] The glass fiber membrane (ultrafine glass fiber membrane for power source battery) and the modified coating of the prepared composite membrane in Example 1 were observed by scanning electron microscope. The results are as follows: Figure 1 and 2 shown.
[0078] Figure 1 is a scanning electron microscope image of the glass fiber membrane in Example 1; Figure 2 This is a scanning electron microscope image of the modified coating in the composite diaphragm prepared in Example 1.
[0079] Figure 3 This is a macroscopic image of the glass fiber membrane in Example 1 and the modified coating in the prepared composite diaphragm.
[0080] from Figures 1 to 3 It can be seen that the modified coating in the prepared composite membrane has a denser surface than that of the glass fiber membrane.
[0081] Sodium vanadium fluorophosphate was used as the positive electrode, metallic sodium was used as the negative electrode, the composite diaphragm prepared in Example 1 was used as the diaphragm, the modified coating was in contact with the negative electrode, the electrolyte was 1M NaClO4 inPC, and a battery was assembled. The coulombic efficiency of the battery after 500 cycles at a 5C rate was as follows: Figure 4 As shown, the discharge capacity is Figure 5 As shown, it can be seen that the battery still has a capacity retention rate of 79.04% after 1000 cycles.
[0082] Sodium vanadium fluorophosphate was used as the positive electrode, metallic sodium was used as the negative electrode, the ordinary glass fiber membrane (ultrafine glass fiber membrane for power supply battery) in Example 1 was used as the diaphragm, the modified coating was in contact with the negative electrode, the electrolyte was 1M NaClO4 inPC, and a battery was assembled. The coulombic efficiency of the battery after 500 cycles at a 5C rate was as follows: Figure 4 As shown, the discharge capacity is Figure 5 shown.
[0083] from Figure 4 and 5It can be seen that compared with the battery using the glass fiber membrane as the diaphragm, the battery using the composite diaphragm prepared in Example 1 as the diaphragm has higher cycle stability and a capacity increase of about 24%.
[0084] Example 2
[0085] The composite diaphragm is composed of a glass fiber membrane and a modified coating layer arranged in layers;
[0086] The modified coating comprises β"-Al2O3 and PVDF, and the mass ratio of β"-Al2O3 to PVDF is 7:1;
[0087] The thickness of the modified coating is 20 μm; the thickness of the glass fiber membrane is 0.8 mm;
[0088] The preparation method of the composite diaphragm comprises the following steps:
[0089] (1) Mg 0.67 Na 1.67 Al 10.33 O 17 For the standard formula, α-Al2O3, MgO and Na2CO3 were weighed, placed in an agate ball mill, ethanol was added, and ball milled at 400 rpm for 4 h to obtain a slurry;
[0090] (2) drying the slurry obtained in step (1) in a drying oven at 60° C. for 8 h, then placing it in a muffle furnace and calcining it at 1200° C. for 1 h, then placing it in a ball mill again, adding ethanol, ball milling at 400 rpm for 4 h, and then drying it in a drying oven at 60° C. for 8 h to obtain β"-Al2O3 powder with a particle size of 0.1 to 1 μm;
[0091] (3) placing the β"-Al2O3 powder obtained in step (2) and PVDF in a ball mill, dropping NMP, and ball milling at 400 rpm for 8 h to obtain a mixed suspension; wherein the mass ratio of PVDF to NMP is 2.5:97.5;
[0092] (4) The mixed suspension obtained in step (3) is evenly coated on one side of the ultrafine glass fiber diaphragm of the power source battery using a scraper, and then placed in a 70° C. oven for drying for 8 hours to obtain a composite diaphragm; wherein the ultrafine glass fiber diaphragm of the power source battery is produced by Qicaiguan; and the coating thickness is 75 μm.
[0093] A battery was assembled in the manner of Example 1, i.e., sodium vanadium fluorophosphate was used as the positive electrode, metallic sodium was used as the negative electrode, the composite diaphragm prepared in Example 2 was used as the diaphragm, the modified coating was in contact with the negative electrode, the electrolyte was 1M NaClO4 inPC, and the battery was assembled. The battery still had a capacity retention rate of 78% after 1000 cycles at a rate of 5C.
[0094] Example 3
[0095] The composite diaphragm is composed of a glass fiber membrane and a modified coating layer arranged in layers;
[0096] The modified coating comprises β"-Al2O3 and PVDF, and the mass ratio of β"-Al2O3 to PVDF is 8:1;
[0097] The thickness of the modified coating is 26 μm; the thickness of the glass fiber membrane is 0.8 mm;
[0098] The preparation method of the composite diaphragm comprises the following steps:
[0099] (1) Mg 0.67 Na 1.67 Al 10.33 O 17 For the standard formula, γ-Al2O3, MgO and Na2CO3 were weighed, placed in an agate ball mill, ethanol was added, and ball milled at 400 rpm for 4 h to obtain a slurry;
[0100] (2) drying the slurry obtained in step (1) in a drying oven at 60° C. for 8 h, then placing it in a muffle furnace and calcining it at 1150° C. for 1 h, then placing it in a ball mill again, adding ethanol, ball milling it at 400 rpm for 8 h, and then drying it in a drying oven at 60° C. for 8 h to obtain β"-Al2O3 powder with a particle size of 0.1 to 1 μm;
[0101] (3) placing the β"-Al2O3 powder obtained in step (2) and PVDF in a ball mill, dropping NMP, and ball milling at 400 rpm for 8 h to obtain a mixed suspension; wherein the mass ratio of PVDF to NMP is 2.5:97.5;
[0102] (4) The mixed suspension obtained in step (3) is evenly coated on one side of the ultrafine glass fiber diaphragm of the power source battery using a scraper, and then placed in a 70° C. oven for drying for 8 hours to obtain a composite diaphragm; wherein the ultrafine glass fiber diaphragm of the power source battery is produced by Qicaiguan; and the coating thickness is 75 μm.
[0103] A battery was assembled in the manner of Example 1, i.e., sodium vanadium fluorophosphate was used as the positive electrode, metallic sodium was used as the negative electrode, the composite diaphragm prepared in Example 3 was used as the diaphragm, the modified coating was in contact with the negative electrode, the electrolyte was 1M NaClO4 inPC, and the battery was assembled. The battery still had a capacity retention rate of 75% after 1000 cycles at a rate of 5C.
[0104] Example 4
[0105] The composite diaphragm is composed of a glass fiber membrane and a modified coating layer arranged in layers;
[0106] The modified coating comprises β"-Al2O3 and PVDF, and the mass ratio of β"-Al2O3 to PVDF is 7:1;
[0107] The thickness of the modified coating is 20 μm; the thickness of the glass fiber membrane is 0.8 mm;
[0108] The preparation method of the composite diaphragm comprises the following steps:
[0109] (1) Mg 0.67 Na 1.67 Al 10.33 O 17 For the standard formula, γ-Al2O3, MgO and Na2CO3 were weighed, placed in an agate ball mill, ethanol was added, and ball milled at 400 rpm for 4 h to obtain a slurry;
[0110] (2) drying the slurry obtained in step (1) in a drying oven at 60° C. for 8 h, then placing it in a muffle furnace and calcining it at 1150° C. for 1 h, then placing it in a ball mill again, adding ethanol, ball milling at 400 rpm for 4 h, and then drying it in a drying oven at 60° C. for 8 h to obtain β"-Al2O3 powder with a particle size of 0.1 to 1 μm;
[0111] (3) placing the β"-Al2O3 powder obtained in step (2) and PVDF in a ball mill, dropping NMP, and ball milling at 300 rpm for 8 h to obtain a mixed suspension; wherein the mass ratio of PVDF to NMP is 2.5:97.5;
[0112] (4) The mixed suspension obtained in step (3) is evenly coated on one side of the ultrafine glass fiber diaphragm of the power source battery using a scraper, and then placed in a 70° C. oven for drying for 8 hours to obtain a composite diaphragm; wherein the ultrafine glass fiber diaphragm of the power source battery is produced by Qicaiguan; and the coating thickness is 75 μm.
[0113] A battery was assembled in the manner of Example 1, i.e., sodium vanadium fluorophosphate was used as the positive electrode, metallic sodium was used as the negative electrode, the composite diaphragm prepared in Example 4 was used as the diaphragm, the modified coating was in contact with the negative electrode, the electrolyte was 1M NaClO4 inPC, and the battery was assembled. The battery still had a capacity retention rate of 70% after 1000 cycles at a rate of 5C.
[0114] It can be seen from the above examples that the composite diaphragm provided by the present invention has excellent resistance to dendrite penetration, and the prepared sodium ion battery has excellent cycle stability.
[0115] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A composite diaphragm comprising a laminated glass fiber membrane and a modified coating; The components of the modified coating include β"-Al2O3 and a binder.
2. The composite diaphragm according to claim 1, characterized in that: The mass ratio of the β"-Al2O3 to the binder is (2-9):
1.
3. The composite diaphragm according to claim 1, characterized in that: The thickness of the modified coating is 10-30 μm; the thickness of the glass fiber membrane is 0.4-2 mm.
4. The method for preparing the composite diaphragm according to any one of claims 1 to 3, comprising the following steps: (1) mixing β"-Al2O3, a binder and a solvent to obtain a mixed suspension; (2) coating the mixed suspension obtained in step (1) on the surface of the glass fiber membrane to obtain a composite diaphragm.
5. The preparation method according to claim 4, characterized in that: The particle size of β"-Al2O3 in step (1) is 0.1 to 1 μm.
6. The preparation method according to claim 4, characterized in that: The mass ratio of the binder to the solvent in the step (1) is (2-3): (97-98).
7. The preparation method according to claim 4, characterized in that: The mixing in step (1) is ball milling mixing.
8. The preparation method according to claim 7, characterized in that: The rotation speed of the ball milling is 200-500 rpm, and the time of the ball milling is 2-8 hours.
9. The preparation method according to claim 4, characterized in that: The coating in step (2) is performed by scraping.
10. Use of the composite diaphragm according to any one of claims 1 to 3 or the composite diaphragm prepared by the preparation method according to any one of claims 4 to 9 in secondary battery diaphragms.
